Judge Frank Creede, Jr. Swears In Superior Court Judge Ralph Nunez - Watkins, Howard::::::::: (1983)
Ralph Nunez, Lucia Nunez, Michelle Nunez, Rachel Nunez, and Judge Frank Creede, Jr. about to administer the oath of office